Early postnatal development of contractile performance and responsiveness to Ca2+, verapamil and ryanodine in the isolated rat heart - Ostádalová, I; Kolár, F; Ostádal, B; Rohlícek, V; Rohlícek, J; Procházka, J (Journal of molecular and cellular cardiology, 1993)
Contractile performance of the isolated perfused rat heart and its inotropic response to Ca2+, verapamil and ryanodine was studied in 1-, 2-, 4-, 7- and 12-day-old animals. Values of the developed force revealed two different phases: a slow decrease from day 1 to day 4 followed by a steep increase up to day 12. A similar biphasic time course was observed in the magnitude of the inotropic effect of Ca2+ (0.6-10.0 mmol.l-1): decrease from day 1 to day 4 followed by an increase up to day 7. The sensitivity to Ca2+ was, however, not changed. An analogous biphasic response was also observed during perfusion with the calcium antagonist verapamil (10(-9) to 3.3 x 10(-7) mol.l-1): the sensitivity to negative inotropic effect rose from day 1 to day 4 and then decreased at day 7 (values of IC50 were 170 +/- 61, 17 +/- 6 and 171 +/- 60 10(-9) mol.l-1 S.E.M. on day 1, 4 and 7, respectively). The contractile response to the inhibitor of calcium release from sarcoplasmic reticulum (SR)--ryanodine (10(-6) mol.l-1)--was surprisingly high already in 1-day-old animals (inhibition of contraction by more than 50%) indicating the presence of functionally active SR in the rat heart just after birth. Our data clearly shows that the early development of contractile function and inotropic responsiveness of the rat heart is not linear and changes dramatically during the first week of life.
Keywords: Calcium; Calcium Channels; Myocardial Contraction; Sarcoplasmic Reticulum; velikost orgánu; verapamil; Dose-Response Relationship, Drug; vápník; stárnutí; krysa rodu Rattus; Verapamil; zvířata; Aging; potkani Wistar; časové faktory; Rats, Wistar; Male; Heart; ryanodin; Ryanodine; kontrakce myokardu; vápníkové kanály; Rats; myokard; vztah mezi dávkou a účinkem léčiva; Animals; Organ Size; sarkoplazmatické retikulum; Myocardium; mužské pohlaví; Time Factors; srdce